2015
DOI: 10.1179/1607845415y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow iron distribution, hepcidin, and ferroportin expression in renal anemia

Abstract: Thus, in anemic epoetin naive non-dialysis CKD patients, hepcidin and ferroportin expression by erythroblast and macrophage are closely related to bone marrow iron distribution. Although the hepcidin-ferroportin system seems regulated by ferritin-driven Hep25, serum hepcidin and peripheral iron indices are of little help in describing bone marrow iron status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
1
25
0
2
Order By: Relevance
“…However, we previously demonstrated that the serum hepcidin level can be exclusively associated with the ferritin level in patients on MHD in the absence of apparent inflammation and independent of the levels of inflammatory cytokines [27] . Several reports have confirmed these observations [28][29][30] . These data suggest that excessive iron storage or administration increases hepcidin levels and accelerates iron sequestration in most of the cells in the body ( fig.…”
Section: Host Factorssupporting
confidence: 71%
“…However, we previously demonstrated that the serum hepcidin level can be exclusively associated with the ferritin level in patients on MHD in the absence of apparent inflammation and independent of the levels of inflammatory cytokines [27] . Several reports have confirmed these observations [28][29][30] . These data suggest that excessive iron storage or administration increases hepcidin levels and accelerates iron sequestration in most of the cells in the body ( fig.…”
Section: Host Factorssupporting
confidence: 71%
“…However, the overall event rate was relatively small, while overall a greater proportion of ESRD participants actually met a more stringent biochemical definition of iron sufficiency during this period. However, we recognize that biochemical measures of iron stores may under-diagnosis deficiency at the bone marrow level,[20] and therefore we cannot exclude the possibility of a greater prevalence of iron deficiency in these participants.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hepcidin does not seem to be an important biomarker for predicting iron needs in patients on hemodialysis (HD) [76]. This finding does seem to be explained by the cause of redistribution of iron, which is not related only to changes in systemic, but probably also due to changes in local levels of hepcidin and/or FPN [77]. In any case, we still do not know the real extent of the value of hepcidin as a marker of renal anemia, especially its role in differentiating between ACD and iron deficient anemia (IDA), which are both present in kidney failure.…”
Section: Role Of Hepcidin In Renal Anemiamentioning
confidence: 99%